Performance Study of CaO-CaF2- and CaO-Al2O3-SiO2-Based High-Efficiency Desulfurizers - Ruihong Cao; Shengtao Qiu; Ting Wu; Haijun Wang (Metals)
In order to reduce the content of harmful impurity sulfur elements in steel to meet the quality requirements of high value-added steel, efficient desulfurization of RH vacuum degassing is essential. Based on the simplex lattice composition design method, the effects of typical compositions on liquidus temperature, sulfur capacity, melting temperature, the effects of typical compositions on liquidus temperature, sulfur capacity, melting temperature, viscosity, and desulfurization rate of CaO-CaF2- and CaO-Al2O3-SiO2-based desulfurizers were studied by thermodynamic calculation, the melting temperature test, and the slag–steel contact experiment. The results show that in CaO-CaF2- and CaO-Al2O3-SiO2-based desulfurizers, the changes in CaF2, MgO, and Al2O3 contents has little effect on the equilibrium S content of molten steel at lower SiO2 contents, whereas, at higher SiO2 contents, the equilibrium S content of the molten steel is greatly increased when the CaF2, MgO, and Al2O3 content is greater than a certain value. Meanwhile, the increase in CaF2 and MgO content reduces the high-temperature viscosity and breaking temperature (corresponding to the turning point on the viscosity–temperature curve) to varying degrees, which results in a better slag fluidity and is favorable to the prevention of crusting. With the increase in Al2O3 and SiO2 content, the breaking temperature of the CaO-CaF2-based desulfurizer is significantly reduced, which is beneficial to preventing crust. However, when the breaking temperature of CaO-Al2O3-SiO2-based desulfurizer increases, part of the slag system has solidified at 1400 °C, which is easy to lead to slag crust when the temperature drops. Comprehensively, for the CaO-CaF2-based desulfurizer, CaO = 60 wt%, CaF2 = 30 wt%, SiO2 = 0–5 wt%, and add a small amount of Al2O3 and MgO, its desulfurization effect is significant. For the CaO-Al2O3-SiO2-based desulfurizer, CaO = 39–57 wt%, Al2O3 = 20–35 wt%, SiO2 = 10–15 wt%, MgO = 4 wt%, CaF2 = 4–8 wt%, its desulfurization effect meets the demand, and it can reduce equipment erosion and environmental pollution.